ChemInform Abstract: Discovery, Development, and Commercialization of Gold Catalysts for Acetylene Hydrochlorination. Issue 9 (February 2016) - Johnston, Peter; Carthey, Nicholas; Hutchings, Graham J.
Abstract: Review: 38 refs.